LOSS OF PROPERTY IN CRIME FROM LIABILITY OR FAILURE - Michael Espinoza Coila (2020)
This original article brief, gives release preliminary results of a study conducted in the year 2014 on the loss of the good obligation from crime or misdemeanor and the restitution of property governed by Peruvian law, therefore it aims to establish the interpretive meaning of Article 1140 of the Civil Code of Peru established that the debtor (author of the crime or offense) is required to pay the value of a good, arising from the commission of the offense or lack the creditor (third party purchaser in good faith), by the legal impossibility to deliver a well that was returned to its rightful owner. This course does not apply when the debtor (the offender) has been in arrears to creditor (third party purchaser in good faith). To reach this result, he came to the knowledge of contract law and criminal law, which allowed us to contextualize the interpretive problem. The investigation employment legal method (legal dogmatic), techniques of legal interpretation and textual records of literature review.